Feminism and protest camps : entanglements, critiques and re-imaginings (Bristol University Press, 2023)
In the wake of a global wave of mobilisation, this book offers an unprecedented interrogation of protest camps as sites of gendered politics and feminist activism. Using international case studies, it develops an intersectional analysis of protest camps and tells new and inspiring stories of feminist organising and agency.